A construção da imagem sertaneja maranhense a partir das leituras de Francisco de Paula Ribeiro - Raimundo Lima dos Santos (2014)
The present work is mainly aimed to show the historical process of identity construction of Maranhão hinterland. For this, part of the memories of Portuguese military Francisco de Paula Ribeiro, who lived and worked in Maranhão in the first decades of the nineteenth century. Is considered here the concept of illustration, in its various aspects, philosophical, economic, political and cultural, as a guiding element of the actions of the military, as well as its own nation, the relationship with Brazil. Although their memories had a practical character, to meet the economic and political interests of Portugal, the descriptions of the region deal with different subjects. His narrative is read, in this work, from four points, namely, economic, political, cultural and geographical aspects. From these themes the hinterland identity is configured over time, in the writings of Maranhão important intellectuals, like Parsondas Oak, Oak and Carlota Dunshee de Abranches. This later generation of intellectuals resumed, so often indirect, Paula Ribeiro some impressions about the region and emphasized, among other things, certain aspects of the culture, economy, politics and regional geography, so that eventually contribute the very identity formation that place.